Pediatric RVOT reconstruction with ePTFE trileaflet valved conduits: a dual-center Chinese study - Luo, Kai; Zhang, Qi-Liang; Zhang, Xiao-Yang; Zhou, Zi-Jie; Pan, Yan-Jun; Zhu, Zhong-Qun; Chen, Qiang; Zheng, Jing-Hao; He, Xiao-Min; Zhang, Wei (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aims to assess the early to mid-term clinical efficacy of expanded polytetrafluoroethylene (ePTFE) trileaflet valved conduits in pediatric right ventricular outflow tract reconstruction for congenital heart disease. Methods We conducted a retrospective analysis of pediatric patients who underwent right ventricular outflow tract (RVOT) reconstruction using ePTFE trileaflet valved conduits at two cardiac centers in China, between January 2017 and June 2023. The main assessment criterion was the functionality of the prosthetic pulmonary valve conduit. Results A total of 162 pediatric patients were included, with follow-up periods ranging from 0.1 to 5 years post-discharge, and a median follow-up duration of 1 year (interquartile range: 1, 2). Three patients (1.9%) required re-operation due to conduit obstruction. During follow-up, pulmonary valve flow velocities were recorded as <3 m/s in 134 patients (82.7%), between 3 and 4 m/s in 24 patients (14.8%), and >4 m/s in 4 patient (2.5%). Mild pulmonary valve regurgitation was noted in 148 patients (91.4%), and moderate pulmonary valve regurgitation was noted in 14 patients (8.6%), with no instances of more than moderate pulmonary valve regurgitation. Conclusion The ePTFE trileaflet valved conduit, known for its accessibility and simplicity in manufacturing, demonstrates favorable early to mid-term clinical outcomes in pediatric RVOT reconstruction.